Desain Sistem Pembangkit Listrik Hybrid Off-Grid Menggunakan Software HOMER Untuk Elektrifikasi Di Desa Suryawangi Kecamatan Labuhan Haji Kabupaten Lombok Timur - Hidayatullah, Harsandi; Adhevina, Ihda; Muljono, Agung Budi (Depertment of Electrical Engineering University of Mataram, 2024)
Energy and environmental problems are major challenge in the world. These problems related to the need to replace conventional fuels with new renewable energy sources. New renewable energy is scattered throughout Indonesia, including geothermal, wind, solar, hydro, and biomass. However, the utilization in the national energy is still low. This study offers a solution to this problem by planning a hybrid powerplant in Suryawangi Village, East Lombok, to serve the electrical energy needs of the village. In this study, solar and microhydro powerplant will be simulated to provide electrical energy using HOMER software. The data needed in this study was taken from BPS data and the global solar atlas. Suryawangi village has hydro energy potential with a 477,97 liters per seconds of Kokok Tebaban water flow and also 4,725 kWh/m2/day solar radiation at coordinates -8Â°39'49